TANNIC ACID-HYALURONIC ACID COATING TO IMPROVE CORROSION RESISTANCE OF IMPLANT MATERIAL BASED ON MAGNESIUM ALLOY AZ31B - Pratama, Aditya
Magnesium and magnesium alloys have good biocompatibility and have close mechanical properties to bone. These characteristics make them suitable as implant materials. The problem with magnesium is has a high corrosion rate due to the reaction between magnesium implants and fluids in the human body. One method to regulate the corrosion rate of magnesium to match bone growth is to create a protective layer on the magnesium surface. In this study, a coating process on magnesium alloys using tannic acid-hyaluronic acid was carried out to increase the corrosion resistance of magnesium alloys. SEM characterization showed that the tannic acid-hyaluronic acid layer was formed due to the chelation between the magnesium surface and tannic acid. Furthermore, adding hyaluronic acid to the layer will cover the cracks caused by coating using tannic acid. The tannic acid-hyaluronic acid layer enhances the hydrophilic properties so that it has a high degree of cell attachment to magnesium alloys. In vitro corrosion testing using Tafel polarization showed that tannic acid-hyaluronic acid coating would reduce the corrosion rate of magnesium alloys from 7,379 mm/years to 0.204 mm/years, thereby increasing corrosion resistance from magnesium alloys. Immersion test in SBF solution showed that the tannic acid-hyaluronic acid layer could bind hydroxyapatite which is beneficial for new bone growth.